APLIKASI DAN DIFERENSIASI PENDIDIKAN ISLAM - Islam, Muhammad Hifdil (Institut Ilmu Keislaman Zainul Hasan Genggong, 2019)
AbstrakThis article explores the use of several Islamic terms, and provides guidance to clarify their use in internal and external discourse. This article describes the typology of Islamic education and the institutions associated with it. It aims to increase understanding of important conceptual differences that depend on subtle language variations such as the differences between Muslim and Muslim education, and between teaching Islam and teaching about Islam. This article then attempts to explain the theoretical conception of